Oliy ta‘limda ixtisoslik modullarini o‗qitish samaradorligini oshirish texnologiyalari (SCIENCE and SOCIETY, 2024)
This article reflects the implementation of the complex didactic goal of the program of specialized modules in higher education, and the provision of a specific module to achieve each of them. Therefore, the content of the module is partially structured into educational elements corresponding to didactic goals, and each educational element should be related to a specific functional element of professional activity. At the same time, the article talks about the organization of modular training on problematic and guided